ANALYSIS OF THE IMPACT OF LACK OF CLASSROOMS ON STUDENTS' CONDUCTIVITY WHILE LEARNING - Kholisah, Nur; Belva Saskia; Novi Suci Dinarti; Levy Rohmatilahi; Deti Rostika (PROGRES PENDIDIKAN, 2024)
The classroom is a very important supporting factor when the learning process takes place. A school must meet the criteria in the National Education Standards (SNP), one of which is the criteria for facilities and infrastructure, especially classrooms. This research aims to analyze the impact of the lack of classroom space on students' conduciveness to learning. Lack of classroom space was identified as an issue that may affect the quality of learning and student well-being. This study was conducted with the aim of providing a better understanding of the impact of a lack of classroom space on the conduciveness of student learning. This research uses a qualitative descriptive research method. The qualitative descriptive research method is a research method that explains or presents data from the results of research that has been carried out. The results of this research show that the lack of classroom space has a negative impact on students' conduciveness to learning. With limited classroom space, students experience difficulty in focusing and concentrating, limited social interaction, and higher stress levels. Apart from that, learning becomes less interactive and students find it difficult to move freely.